Astronomiya kursın xabar-kommunikaciyalıq texnologiyaları ortalıǵında oqıtıw metodikası (ulıwma astronomiya bólimin oqıtıw mısalında) - Embergenova, K (SCIENCE and SOCIETY, 2021)
The article discusses the advantages of information and communication technologies in the educational process, pedagogical skills of a teacher in the educational process.
Keywords: astronomy; information and communication technology; web page; student; simulator; sun; spectrum